Assessing Older Community Members Using a Social Work Tool: Developing an Organizational Response. (August 2022) - Ogrin, Rajna; Meyer, Claudia; Karantzoulis, Aliki; Santana, Isabel Jane; Hampson, Ralph
Social Worker's undertake psycho-social assessments and facilitate access to evidence-informed psychological and practical supports to optimize the physical, psychological, and social wellbeing of the community members in their care. Social workers employed at an aged and community care organization undertook a review of the gray and peer reviewed literature and did not identify any existing evidence-based tools. However, 10 key domains were identified from the search. Gaps in the domains were discovered, together with the need for guidance and prompts for less experienced staff and students. Five Social Workers, using co-design principles, reviewed the domains, and added further domains from their social work practice. An evidence-based assessment tool was developed which incorporated 11 domains. The tool can be used to assess the needs of people living in the community who are older and/or have compromised health and wellbeing. Further work is required to pilot test the tool.